Transformasi Digital Pembelajaran: Mengoptimalkan Hasil Belajar Kognitif melalui Multimedia Berbasis Google Sites - Aditia Guntur; Abd. Kahar; Handy Ferdiansyah (Science and Education Journal (SICEDU), 2026)
This study aims to produce a product by developing multimedia learning assisted by Google Sites and to determine the level of validity, practicality, and effectiveness on students' cognitive learning outcomes. This study uses a Mix Method research approach with the type of Research and Development (R&D) research using the ADDIE development model consisting of five stages, namely analysis, design, development, implementation, and evaluation. The research subjects were grade XI students at MA Negeri Sidenreng Rappang. Data collection techniques used questionnaires, observations, and learning outcome tests. The results of the study showed that based on expert assessments of media and multimedia learning materials assisted by Google Sites were in the very valid category. The level of practicality was in the very practical category. Meanwhile, the results of the N-Gain test showed a fairly effective category value. Thus, multimedia learning assisted by Google Sites is suitable for use in mathematics learning.